Strategic development of rural halal tourism using the Business Model Canvas framework: A case study from East Java, Indonesia - Ukhrowi, Mukhamad Zahid (Journal of Islamic Economics Management and Business (JIEMB), 2023)
This article highlights the significance of villages in local governance, especially their potential in tourism, which can drive economic benefits and community development. The purpose of this research is to analyze the development strategy of Sidomulyo Village towards halal tourism using the Business Model Canvas (BMC) approach. The methodology involves a qualitative field research design with data collected through structured interviews, direct observations, and documentation reviews in Sidomulyo Village, East Java. The findings reveal that Sidomulyo Village has significant potential as a halal tourism destination due to its rich natural resources, cultural heritage, and established tourist attractions such as educational tours, batik houses, and coffee industry tours. The village’s strategic use of BMC elements such as value propositions, customer segments, channels, and key partnerships can enhance its appeal to both local and international tourists. Implications of this study suggest that Sidomulyo Village can achieve sustainable economic growth and community welfare by leveraging strategic planning and cost management, thus positioning itself as a unique halal tourism destination.